Molecular breeding for stress tolerance in sesame - Weldemichael, Micheale Yifter; Gebremedhn, Hailay Mehari; Runo, Steven; Gandhi, Harish (Springer, 2025)
Sesame (Sesamum indicum L.) is a vital oilseed crop known for its high-quality edible oil, proteins, minerals, and vitamins. It is primarily cultivated in arid and semi-arid regions, where unpredictable drought poses a major constraint to its production. Sesame is a valuable source of healthy vegetable oil, attracting growing interest worldwide. However, its cultivation in dry regions makes it vulnerable to various biotic and abiotic stresses. Sesame is grown for food, pharmaceutical, medicinal, and industrial uses, which is cultivated as a main cash crop by African and Asian smallholder farmers. Despite its importance, sesame production and productivity remain low due to numerous challenges such as; drought, salinity, diseases, insect pests, inherent genetic problems, and poor agronomic and postharvest practices. Fortunately, the crop's extensive genetic diversity offers potential for enhancing stress resilience. Our understanding of sesame molecular responses will be facilitated by ongoing attempts to develop methods for quantifying biotic and abiotic stresses. We review recent advances in the molecular mechanisms underlying sesame's tolerance to biotic and abiotic stresses focusing on stress-related genes and key agronomic traits. Additionally, we review recent advancements in functional genomics and transcriptomics, specifically in deciphering sesame's responses to drought, water-logging, temperature fluctuations, osmotic stress, and salinity as well as biotic stressors. To accelerate the development of stress-resistant sesame varieties, we propose advancing research in genomics-assisted breeding. Approaches such as genome-wide association studies (GWAS) and high-density linkage mapping can help identify key genetic markers associated with stress tolerance. These markers can then be applied in marker-assisted selection to develop resilient cultivars, ensuring stable yields under changing climate conditions.